Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/mpg.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Symptoms and Disease Severity in Children and Adolescents With Crohn Disease

Abstract: Implementing a brief anxiety screen in tertiary pediatric settings may be one approach to identify young patients with CD in distress. Health care providers should consider periodic assessment of school anxiety among youth with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
3
37
1
2
Order By: Relevance
“…16 Both anxiety and depression are increased among patients with IBD compared with other disease states and the general population. 1719 In addition, anxiety has been associated with worse outcomes among pediatric patients with IBD 20 and increased resource utilization among adult patients with IBD. 21,22 Although the impact of these psychological comorbidities has been evaluated in multiple studies, a majority of patients with UC or CD may not receive adequate psychosocial support in the scheme of their overall treatment for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…16 Both anxiety and depression are increased among patients with IBD compared with other disease states and the general population. 1719 In addition, anxiety has been associated with worse outcomes among pediatric patients with IBD 20 and increased resource utilization among adult patients with IBD. 21,22 Although the impact of these psychological comorbidities has been evaluated in multiple studies, a majority of patients with UC or CD may not receive adequate psychosocial support in the scheme of their overall treatment for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Although depression and anxiety were not specific targets of intervention, higher prevalence of these psychological problems has been reported in children with IBD as noted in the introduction 18,19 and it was of interest to determine if an intervention to improve stress management and coping might have secondary effects on psychosocial function. Children in both conditions reported significant improvement on psychosocial functioning and depression symptoms with no difference between groups.…”
Section: Discussionmentioning
confidence: 99%
“…7,13-17 Typical of these, recently Reigada et al 18 found that anxiety symptoms were significantly associated with moderate/severe disease activity among children and adolescents with CD. Similarly, Srinath et al 19 found that depression was a significant predictor of abdominal pain in children and adolescents with IBD, perhaps more so in UC than in CD.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8] Moreover, several researchers have reported that youth with IBD may be at risk for anxiety symptoms. 7,13,14 However, not all studies have corroborated the findings of increased risk of internalizing symptoms among youth with IBD. 9 The inconsistencies in findings across studies are likely related to several factors.…”
mentioning
confidence: 87%
“…10,18 Similarly, youths with moderate-to-severe disease activity have been shown to be at risk for higher levels of anxiety symptoms relative to those with no or mild disease activity. 14 This study aimed to expand the existing research by examining rates of depressive symptoms, anxiety symptoms, and overall internalizing symptomatology in a relatively large, multisite sample of youth with IBD. Of note, we focused on a sample of youth with established diagnoses who were on oral medications and who had low levels of disease activity.…”
mentioning
confidence: 99%